PENGARUH PERBANDINGAN LEMAK KAKAO (Theobroma cacao L.) DAN VCO (Virgin Coconut Oil) SERTA LAMA PENGADUKAN TERHADAP KARAKTERISTIK MARGARIN - saraswati, gusti agung ayu kade; Wrasiati, Luh Putu; Triani, I Gusti Ayu Lani (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
Cocoa fat are composed of vegetable fat which is contain high stearate acid and palmitate acid and usualy used at pharmacy sector as a suppositoria , in indutrial sector it use as cosmetic based such as lipstick and lip balm, and in food sector it used as a mixing ingredient of chocolate bar, candy, and bakery. VCO (Virgin Coconut Oil) is a clear oil from fresh coconut extraction proces which is contain high antioxidant and laurate acid that good for health benefit. In this study we will learn about comparation effect of cocoa butter and VCO and mixig duration to margarne characteristic. The comparation of cocoa butter and VCO are 65:35, 70:30, and 75:25 and the mixing duration are 10 minute, 15 minute, 20 minute. The result show the increase of cacao butter make margarine have a higer fat contain, texture, and chocolate taste. The resutlt show that both comparation of ingridient and mixing duration give a real imppact to margarine charasteristic. In this study the best treatment is in comparation cacao butter and VCO at 70:30 and with mixing duration for 15 minute. The best margarine characteristic having a result water content14,46±0,37%, fat content90.42±0.61%, texture analyzer2.74 ± 0.19 %, color intencity test L* 34.23±0.04%, a* 17.6 ±0.25%, b* 19.34±0.25% and scoring color 3.40 ±0.51%, taste 3.30 ± 0.51%, and favorites 3.00 ± 0.65 %.